Hardware implementation of Predictive Torque Controlled Open-end winding induction motor drive with self-tuning algorithm. Issue 1 (1st January 2017) - Praveen Kumar, Kunisetti V.; Ravi Eswar, K.M.; Kumar, Thippiripati Vinay
Abstract: Predictive Torque Control (PTC) is an acceptable alternate to Direct Torque Control (DTC) of induction motors. The limitation of classical PTC is selection of weighting factor, improper selection of weighting factors lead to distortions in current, voltage, high torque and flux ripple. In classical PTC, to reduce torque and flux ripples manual tuning of weighting factors is needed and weighting factors are selected empirically. To circumvent tedious tuning process of weighting factor, this article proposes a new self-tuned PTC algorithm to Open End Winding Induction Motor (OEWIM) drive. OEWIM's are more popular in electric vehicles, ship propulsion but they require ripple free torque. A new self-tuned PTC algorithm is implemented to OEWIM with multi-level inversion to reduce torque and flux ripples. The effectiveness of proposed PTC algorithm was tested by applying it to multi-level inverter fed OEWIM drive through simulation and experimental verification.